PENINGKATAN KERAGAMAN PEMBELAJARAN MELALUI KOMUNIKASI ANTARBUDAYA DI LINGKUNGAN PENDIDIKAN - Sabila Putri Sutrijadi; Rizang Conery (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to explore the role of intercultural communication in enhancing diversity in learning within the educational environment in Indonesia. The research method employed is a descriptive qualitative approach focusing on the interaction among students from different cultural backgrounds. The results indicate that intercultural communication can facilitate an inclusive learning process, promote tolerance, and reduce discrimination in the educational setting. The conclusion drawn from this study emphasizes the importance of considering intercultural communication aspects in creating a diverse and inclusive learning environment.